Demand for child care and female employment in Colombia (2004)
Due to the increase in labor force attachment of mothers of young children in the last decade, child care policies have a renewed importance. This paper uses Colombian data to perform a characterization of the child care market, generating stylized facts to inform the debate. The main trends are: highly informal market, high participation and employment rates of mothers of young children, relatively little "unmet need" for child care services and the poor facing constraints to access the market for child care, both in quantity and price. This study analyzes how Colombian families make their child care decisions, simultaneously choosing whether the mother works, whether to pay for care and what mode to use. The estimations performed suggest that there is a strong positive effect of child care choice on the mother's working decision, and that this effect is much higher for low-income families. As children grow the availability of formal care modes becomes determinant to enable the mother's labor force attachment.